2021
DOI: 10.17309/tmfv.2021.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Anthropometric Characteristics and Health-Related Physical Fitness in Macedonian Children: the Makfit Studies

Abstract: The purpose of the present study was to analyze the secular trends in anthropometric characteristics and health-related physical fitness (i.e., flexibility, muscular strength and speed/agility) in Macedonian children between 2012 and 2019. Materials and methods. We analyzed the secular trends in anthropometric characteristics and health-related physical fitness in Macedonian children between 2012 and 2019. Two representative population studies were conducted 7 years apart in children (6-10 years) from Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The results of this study are in line with the findings of previous studies (Elezi et al, 2021; Fühner et al, 2021; Tomkinson et al, 2019). Importantly, in a recently published systematic review, it has been suggested that the secular decrease in the physical fitness of youth occurred primarily over the last decade, which is exactly the time span included in the current study (Fühner et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study are in line with the findings of previous studies (Elezi et al, 2021; Fühner et al, 2021; Tomkinson et al, 2019). Importantly, in a recently published systematic review, it has been suggested that the secular decrease in the physical fitness of youth occurred primarily over the last decade, which is exactly the time span included in the current study (Fühner et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, an increase in flexibility, abdominal muscles strength, coordination, speed and agility was noted among children from Macedonia, between 2012 and 2019. Nevertheless, also a decrease in the explosive force of the lower limbs was observed (Elezi et al, 2021). Similarly, in Slovenian children, there was a decrease in muscular fitness, leg power and arm strength between 1983 and 2014, while core muscle strength mostly increased (Đuri c et al, 2021).…”
Section: Boysmentioning
confidence: 99%
“…Physical education is an important factor in the development of schoolchildren's personal qualities and a healthy lifestyle (Krutsevich, et al 2021;Cisterna, et al, 2019;Elezi, et al, 2021). Motor skills development in schoolchildren is the main task of the modern school (Ivashchenko, 2020;Kapkan et al, 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The design used -comparing athletes who differ in skill level -is widely used in sports science. A similar approach was used in works (Podrigalo et al, 2020;Volodchenko et al, 2017;Elezi et al, 2021). It allows us to highlight factors and qualities of a higher level.…”
Section: Discussionmentioning
confidence: 99%